2016
DOI: 10.1158/1078-0432.ccr-16-0149
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Conditionally Reprogrammed Patient-Derived Carcinoma Cells Identifies ERCC3–MYC Interactions as a Target in Pancreatic Cancer

Abstract: Purpose Even when diagnosed prior to metastasis, pancreatic ductal adenocarcinoma (PDAC) is a devastating malignancy with almost 90% lethality, emphasizing the need for new therapies optimally targeting the tumors of individual patients. Experimental Design We first developed a panel of new physiological models for study of PDAC, expanding surgical PDAC tumor samples in culture using short-term culture and conditional reprogramming with the Rho kinase inhibitor Y-27632, and creating matched patient-derived x… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 49 publications
(72 reference statements)
3
57
0
Order By: Relevance
“…Patient-derived cell lines via CR can be rapidly established [203] and are suitable to screen large drug libraries [204, 205], or to test drug combinations to overcome acquired resistance to targeted therapy [206]. While phenotypic features and the genetic heterogeneity of the original tumor are retained in short term CR cultures, the enrichment of specific cell populations, including non-transformed epithelial cells in this model, requires cross-verification of pheno- and genotypic features of donor tissues and CR cells.…”
Section: The Use Of In Vitro and In Vivo Models For Guiding Precisionmentioning
confidence: 99%
“…Patient-derived cell lines via CR can be rapidly established [203] and are suitable to screen large drug libraries [204, 205], or to test drug combinations to overcome acquired resistance to targeted therapy [206]. While phenotypic features and the genetic heterogeneity of the original tumor are retained in short term CR cultures, the enrichment of specific cell populations, including non-transformed epithelial cells in this model, requires cross-verification of pheno- and genotypic features of donor tissues and CR cells.…”
Section: The Use Of In Vitro and In Vivo Models For Guiding Precisionmentioning
confidence: 99%
“…In tumor CR cell cultures, phenotypic and genotypic features of the primary tumor are maintained 7 and the technique has recently been used to identify an appropriate therapy for respiratory papillomatosis 14 . Therefore, it is clear that potential applications of the CR method are far-reaching, and, as described by independent laboratories, it can be adapted for live biobanking 7 and basic research 1521 , as well as for diagnostic 22,23 , therapeutic 21,24,25 and regenerative medicine 21,26,27 …”
Section: Introductionmentioning
confidence: 99%
“…However, PDX takes many months to establish and is difficult to use for high‐throughput screening in cancer patients . Because of these limitations, a recent patient‐derived cancer cell line model, CRCs, are extensively used in cancer research . CRCs induce the propagation and immortalization of human tumor epithelial cells and generate patient‐specific cell lines within 2 or 4 weeks .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, several preclinical models have been used for drug sensitivity tests, subtype specific functional analysis, and drug development for various cancers, including PDAC. 3,15,16 Previous studies have reported their results using patient-derived xenografts (PDX) as representative preclinical models. However, PDX takes many months to establish and is difficult to use for high-throughput screening in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation